The enjoyment of music : - Machlis, Joseph (W.W. Norton, 2003)
Used by more than 3.5 million students, The Enjoyment of Music has been the most trusted introduction to music for over five decades. The Tenth Edition reaffirms this status in a thoughtful revision offering a more diverse repertory and a stronger emphasis on the cultural significance of musical styles and periods.